2012
DOI: 10.5539/gjhs.v5n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Exposure to Lead in Tap Water among Residents of Seri Kembangan, Selangor state, Malaysia

Abstract: Introduction:A cross sectional study was conducted to estimate risk of exposure to lead via tap water ingestion pathway for the population of Seri Kembangan (SK).Methodology:By using purposive sampling method, 100 respondents who fulfilled the inclusive criteria were selected from different housing areas of SK based on geographical population distribution. Residents with filtration systems installed were excluded from the study. Questionnaires were administered to determine water consumption-related informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Such a large difference is due to a high Pb concentration in drinking water. In Lim et al’s study, as in our study, the R was observed less than 1 which this issue is due to the proximity of lead concentration in this study, which is 3.04-6.697 µg/l with our study ( Lim, Shaharuddin, & Sam, 2012 ). Also, in Rajaei et al’s study, the HQ was 0.00007 which was observed less than 1 as in our study ( Rajaei, Pourkhabaz, & Hesari Motlagh, 2012 ).…”
Section: Discussionsupporting
confidence: 49%
“…Such a large difference is due to a high Pb concentration in drinking water. In Lim et al’s study, as in our study, the R was observed less than 1 which this issue is due to the proximity of lead concentration in this study, which is 3.04-6.697 µg/l with our study ( Lim, Shaharuddin, & Sam, 2012 ). Also, in Rajaei et al’s study, the HQ was 0.00007 which was observed less than 1 as in our study ( Rajaei, Pourkhabaz, & Hesari Motlagh, 2012 ).…”
Section: Discussionsupporting
confidence: 49%
“…The selected study area was in Taman Seri Serdang whereby this area was estimated with population of 14360 people by the Local Planning of Subang Jaya (Lim, Shaharuddin, Sam, 2012). In this area, there are residential area, commercial area and a secondary school with the estimated area is 0.2km 2 .…”
Section: Study Areamentioning
confidence: 99%
“…Moreover, the Pb concentration at Bandar Sunway crossed the maximum limit of drinking water quality standard 10 µg/L proposed by Ministry of Health Malaysia, World Health Organization, and European Commission, respectively as well as 15µg/L by United States Environmental Protection Agency. However, lower dissolved Pb concentrations were also observed 3.04 µg/L at Seri Kembangan et al [7], 0.75 µg/ Lat Kuala Lumpur [6] and 3±2 µg/L in Langat Basin [13] than the concentration at Bandar Sunway within the Langat River Basin. The higher Pb concentration in the supply water might be primarily from corrosion of the galvanized iron (i.e.…”
Section: Dissolved Pb Concentration In Raw Watermentioning
confidence: 99%
“…zinc coated) pipe [26-28] as well as PVC pipe where Pb used as a stabilizer for manufacturing [29]. Moreover, the combination of copper piping with lead solder at the household level can produce galvanic corrosion to leach lead even in relatively noncorrosive water [7].…”
Section: Dissolved Pb Concentration In Raw Watermentioning
confidence: 99%
See 1 more Smart Citation